2019
DOI: 10.1044/pers-sig2-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Spring EngAGEment: An Interprofessional Collaboration to Enhance Community Interaction and University Education

Abstract: Purpose Interprofessional education and practices are increasingly recognized as vital to addressing complex health needs, including individuals living with Alzheimer's disease or other associated dementias (AD/OAD). An innovative approach to meet this need is to create a meaningful engagement experience, Spring EngAGEment, following a multidisciplinary patient-centered model to serve individuals with AD/OAD and their care partners in the community and to offer new interprofessional collaboration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Analysis of included articles demonstrated that the nursing profession was the most frequently represented (n = 27), 22‐48 followed by medicine (n = 20), 24,26,27,29,30,32,34‐36,38,40‐44,46‐50 and pharmacy (n = 14) 22,24‐26,28,29,31,41,43,44,50‐53 . A large number of studies were undertaken in the United States of America (n = 24), 22‐25,28‐33,36‐41,45,49‐52,54‐56 with a smaller number from Australia (n = 4), 34,43,57,58 Canada (n = 3) 53,59,60 and the United Kingdom (n = 2) 42,47 (see Appendix ). Acquisition of knowledge was the most commonly assessed outcome (n = 17), 24,26‐29,32,33,35,38,39,43‐45,49,53,55,57 followed by behaviour change (n = 17), 22,25,30‐32,36,37,40,41,44,45,50,55,56,58‐60 benefit to patients (n = 11) 23,34,39,42,46‐48,51,52,54 and acquisition of skills (n = 3) 25,30,31 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis of included articles demonstrated that the nursing profession was the most frequently represented (n = 27), 22‐48 followed by medicine (n = 20), 24,26,27,29,30,32,34‐36,38,40‐44,46‐50 and pharmacy (n = 14) 22,24‐26,28,29,31,41,43,44,50‐53 . A large number of studies were undertaken in the United States of America (n = 24), 22‐25,28‐33,36‐41,45,49‐52,54‐56 with a smaller number from Australia (n = 4), 34,43,57,58 Canada (n = 3) 53,59,60 and the United Kingdom (n = 2) 42,47 (see Appendix ). Acquisition of knowledge was the most commonly assessed outcome (n = 17), 24,26‐29,32,33,35,38,39,43‐45,49,53,55,57 followed by behaviour change (n = 17), 22,25,30‐32,36,37,40,41,44,45,50,55,56,58‐60 benefit to patients (n = 11) 23,34,39,42,46‐48,51,52,54 and acquisition of skills (n = 3) 25,30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies were undertaken in the United States of America (n = 24), 22‐25,28‐33,36‐41,45,49‐52,54‐56 with a smaller number from Australia (n = 4), 34,43,57,58 Canada (n = 3) 53,59,60 and the United Kingdom (n = 2) 42,47 (see Appendix ). Acquisition of knowledge was the most commonly assessed outcome (n = 17), 24,26‐29,32,33,35,38,39,43‐45,49,53,55,57 followed by behaviour change (n = 17), 22,25,30‐32,36,37,40,41,44,45,50,55,56,58‐60 benefit to patients (n = 11) 23,34,39,42,46‐48,51,52,54 and acquisition of skills (n = 3) 25,30,31 . No studies were found focusing on organisational change as an outcome.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations